2013
DOI: 10.1038/bjc.2013.402
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of ovarian and fallopian tube cancer by examination of cytological samples from the endometrial cavity

Abstract: Background:Accumulating evidence suggests that many ovarian high-grade serous carcinomas (HGSCs) originate in the fallopian tube. Malignant cells shed by tubal lesions can be detected by examination of cytological samples from the endometrial cavity (endometrial cytological testing). To evaluate the use of this method for detecting HGSC, we examined epithelial ovarian, fallopian tube, and primary peritoneal cancer patients.Methods:Endometrial cytological testing was performed for endometrial cancer screening i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 34 publications
(60 reference statements)
0
57
1
Order By: Relevance
“…However, the character of the whole structure of the specimen, followed by the visual examined is the principal step used by pathologists in the diagnosis of the abnormal tissue 1 . In addition, the cytological examination has also played an important role in the diagnosis of cancer 4 , and its results could be helpful for confirming of the histological examination 13,22 . Although the cytological analysis has many disadvantages [23][24] , it also has several benefits compared with the pathological analysis, including cost-effectiveness, rapid turnaround time, providing a minimal risk for the patient, and giving the results when other techniques failed 1,4 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the character of the whole structure of the specimen, followed by the visual examined is the principal step used by pathologists in the diagnosis of the abnormal tissue 1 . In addition, the cytological examination has also played an important role in the diagnosis of cancer 4 , and its results could be helpful for confirming of the histological examination 13,22 . Although the cytological analysis has many disadvantages [23][24] , it also has several benefits compared with the pathological analysis, including cost-effectiveness, rapid turnaround time, providing a minimal risk for the patient, and giving the results when other techniques failed 1,4 .…”
Section: Resultsmentioning
confidence: 99%
“…The first one is the accuracy in detection of cancer compared with that obtained with other methods 4,[6][7]10 and the ability to differentiate between benign and malignant disease 18,25 . Furthermore, the assistance of other methods for detection of cancer is another benefit of histopathological examination as it increases the sensitivity of PSA in the detection of the prostate cancer 26 or preliminary diagnosis of basal cell carcinoma based on the appearance 20 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study involving 122 suspected cancer patients found five patients with positive endometrial cytologic results displaying early neoplastic change. In another study, Otsuka et al showed that patients with high-grade serous ovarian carcinomas were significantly more likely to have positive endometrial cytology compared with other histological subtypes (23% vs 6%, p=0.02) 34. Alternatively, molecular cancer signatures have also been picked up in uterine lavage fluid.…”
Section: Ca125 Screenmentioning
confidence: 99%
“…The early detection of an STIC can help in the prevention of invasive ovarian cancers; however, no screening techniques are currently available to detect STIC. Endometrial cytological testing may detect early-stage ovarian, tubal, and peritoneal HGSCs and may be useful for ovarian cancer screening, but this study needs further validation 82. The inclusion of patients with FTC, PPC, and HGSC of the ovary in clinical trials is recommended as they have similar molecular abnormalities and likely the same cell of origin.…”
Section: Future Directionsmentioning
confidence: 99%